Useful technique for submucous myomectomy under direct transcervical resectoscope observation - Tatsuji Hoshino; Masumi Yanagawa; Aya Usuki Matsubayashi; Shinya Yoshioka (Wolters Kluwer Medknow Publications, 2017)
The transcervical resectoscope (TCR) is used for resecting a submucous myoma (SMM). Safe grasping of an SMM with forceps and its complete resection under transabdominal ultrasound (TAUS) guidance is not always easy. SMMs are slippery, making them difficult to grasp. The SMM moves right to left and anterior to posterior when the surgeon tries to grasp it with placental forceps. Surgeons could use small Martin forceps (65% smaller) to grasp SMMs safely and tightly under direct TCR (transcervical resectoscope) observation. We present a case in which this operative procedure was used to remove an SMM with Figure and Video. The benefits of this procedure are enormous and could be immeasurably important to hysteroscopists and gynecologists.